Are We Out Of The Woods Yet? An Analysis Of Figurative Expressions Utilized In Taylor Swift’s 1989 Album - Nursyaheedah, Muhammad Isa; Amy Zulaikha, Mohd Ali; Fathiah Izzati, Mohamad Fadzillah; Hanisah, Kasbon (JHLCB, 2017)
The study focuses on the descriptive analysis of figurative expressions utilized in lyrics of Taylor Swift’s 1989 album. According to Carroll (2008), the use of language where the semantic features of the lexicon do not literally relate to the context is known as figurative language. Figurative expressions can often be found in lyrics and is an interesting aspect of a language to discuss. Although previous studies reveal various significant aspects of figurative expressions in pop songs, in particular, there has not been substantial examination of the use of connotation, the device that conveys non-literal or indirect meanings in different dimensions, emotions, and attitudes in these songs. Using the language figuratively is a technique of creating connotative meaning and gives meaningful message to certain audience with the need of interpretation (Suriyawongpaisal, 2013). Hence, it is the interest of this study to focus on the types of figurative expressions and further explore the connotations expressed through figurative expressions in her songs. To conduct this study, all the lyrics of thirteen songs in the 1989 album were identified and classified according to each figurative expressions. A qualitative research with descriptive analysis was used as the method of data analysis. This paper utilizes the 11 types of figure of speech proposed by Kennedy (1979) which are metaphor, simile, personification, hyperbole, synecdoche, metonymy, irony, oxymoron, litotes, paradox, and symbol. This study concludes with recommendations for future research and is expected to make a contribution to the literature of figurative expressions especially for but not limited to pop songs.